Business Transformation of Palasari Tradisional market - Imaduddin, Musa Mujaddid; Dhewanto, Wawan (Journal of Business and Management, 2014)
The growth of traditional market as trading center indicates that there is a growth and economic development in Indonesia. However, traditional markets have various weaknesses that have become the basic character which is very difficult to change, like design factors and market appearance. As the experience, traditional market under managed by government will be faster to develop if get cooperation to private sectors. Such cooperation is manifested in the form of the agreement such as build operate and transfer (BOT) as an alternative solution which is mutually beneficial cooperation. Palasari market in Bandung is one of market where the private sectors could cooperate with government through BOT system. Private sectors could add real estate business on the available area. After doing the research, Palasari area is suitable for apartment business. So, this BOT system is made with construction scheme of market constructing on the ground floor and apartment construction on the floor above. This model business need to be transformated in phisical, system, and cultural aspect. After doing the calculation in financial aspect, this business transformation project is feasible to implement. Implementation of this business transformation also change the culture and system in management of market. Government can restructure its management system related the management of market. Goal of this business transformation is aiming to increase the welfare of traders.Keywords: Bandung, Market, Development, Build-Operate-Transfer, Apartment, Business Transformation